2007
DOI: 10.1002/dir.20072
|View full text |Cite
|
Sign up to set email alerts
|

Nonprice antecedents of consumer preference for cyber and extension brands

Abstract: Price is an important factor affecting consumer preference for online brands and, not surprisingly, has played a dominant role in the Internet marketing literature. Concurrently, important nonprice factors that account for individual online brand preferences have received scant attention. This research examines nonprice influences on preferences for online brands and demonstrates that brand character, brand offerings, prior Internet shopping experience, brand familiarity, and brand evaluation affect online bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
5
0
6
Order By: Relevance
“…Scholars argued that the existing theory needs fresh knowledge given that (1) consumers' cross-channel shopping behaviors are often neglected (Van, Sebastine, & Datch, 2005); (2) theoryguided empirical studies of consumer trust in online shopping are relatively rare (Lee & Turban, 2001);and (3) there are few studies associated with brand familiarity in the e-commerce market (Sääksjärvi & Samiee, 2007). Although previous studies have asserted that consumer trust is the decisive factor in successful e-commerce (Grewal, Hardesty, & Iyer, 2004) and consumer familiarity is a key determinant of their trust toward the Webstore (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars argued that the existing theory needs fresh knowledge given that (1) consumers' cross-channel shopping behaviors are often neglected (Van, Sebastine, & Datch, 2005); (2) theoryguided empirical studies of consumer trust in online shopping are relatively rare (Lee & Turban, 2001);and (3) there are few studies associated with brand familiarity in the e-commerce market (Sääksjärvi & Samiee, 2007). Although previous studies have asserted that consumer trust is the decisive factor in successful e-commerce (Grewal, Hardesty, & Iyer, 2004) and consumer familiarity is a key determinant of their trust toward the Webstore (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the present research is both of theoretical and practical relevance: our results show that the md -IAT procedure is a methodologically sound extension of the IAT that—unlike the latter—also allows for multi-dimensional assessment of brand attitudes. This in turn opens up numerous possibilities for researchers to test constructs such as brand or product personality [9] , [10] , or more generally, consumers' brand associations or attitudes on any kind of multi-dimensional scale [11] . In addition, we show that the md -IAT, just like the IAT, is not affected by the specific stimuli selected to represent a brand.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the dependent variables in this experiment were risk perception, multiple attitude measures, including attitude toward the Web site, attitude towards the online retailer, and behavioral intentions. Furthermore, in the second experiment, several individual characteristics related to online behavior were assessed, because a number of studies have shown that differences in prior online purchase behavior, educational level, Internet access, and frequency of Internet usage may affect online consumer behavior (e.g., Brown, Pope, & Voges, 2003;Chiang & Dholakia, 2003;Crisp, Jarvenpaa, & Todd, 1997;Sääksjärvi & Samiee, 2007;Swinyard & Smith, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pope, & Voges, 2003;Chiang & Dholakia, 2003;Crisp, Jarvenpaa, & Todd, 1997;Sääksjärvi & Samiee, 2007;Swinyard & Smith, 2003).…”
mentioning
confidence: 99%